Aniridia in Two Related Tennessee Walking Horses - Karen A. McCormick; Daniel Ward; Kimberly M. Newkirk (Case Reports in Veterinary Medicine)
Aniridia in horses is rare and has previously been reported to be genetically transmitted in Belgian horses and Quarter horses. This paper describes the defect in 2 related Tennessee Walking horses, with special reference to new findings regarding the molecular genetics of ocular development and how they might relate to equine aniridia. In addition to aniridia, these 2 horses possessed additional ocular abnormalities including cataracts and dermoid lesions. Euthanasia was elected, and the eyes were examined histologically. Iris hypoplasia, atypical dermoids, and cataracts were confirmed in both horses. Due to the heritability of aniridia in horses, breeding of affected animals is not recommended.